DOSES OF JITIRANAS IN COVERAGE AS GREEN MANURE IN PRODUCTIVITY OF LETTUCE - Linhares, Paulo César Ferreira; Azevedo Henriqu, Gabrielly Paula de Souza; Pereira, Maria Francisca Soares; Oliveira, Bruna Solano de; Maracajá, Patrício Borges (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2010)
Aiming to evaluate the agronomic characteristics of lettuce (Lactuca sativa L.), curly type, was performed an experiment in the greenhouse of the experimental area of the garden, of the Department of Plant Sciences, Rural Federal University of Semi-Arid (UFERSA), state of Rio Grande do Norte, Brazil. It was used a complete randomized design with seven treatments and four repetitions, totaling 28 experimental units. The treatments were constituted by: T1 (no fertilizer), T2 (22,8g dry jitirana in coverage), T3 (45,6g of dry jitirana coverage) and T4 (68,4g of dry jitirana in coverage), T5 (91,2g dry jitirana in coverage), T6 (114,0g of dry jitirana in coverage) and T7 (456g of cattle manure). The harvest happened 35 days after the transplanting, it’s been evaluated the characteristics: plant high, number of leaves, the mass of the fresh and dry matter per vase. The increasing of the shoot part and the increasing of fresh matter in the leaves of the plants were statistically superior to control and the regression indicates the possibility of utilization of these doses of jitirana.